Heat Transfer Analysis on Finned Plate Air Heating Solar Collector for its Application in Paddy Drying. (March 2017) - Bhattacharyya, T.; Anandalakshmi, R.; Srinivasan, K.
Abstract: The performance of an extruded finned plate air heating solar collector is studied theoretically for paddy drying applications. Climatic conditions and solar radiation data are accounted based on Guwahati region (26.11˚N, 91.72˚E). Outlet air temperature and pressure drop are considered as controlling parameters to find optimum number of fins, fin height and fin thickness. Outlet air temperature increases and then decreases with number of fins whereas pressure drop increases with number of fins. The analysis showed that finned plate air heating solar collector with 80 fins, 0.6 Height (H) to-Duct length (D) ratio and 2 mm fin thickness yield best results for paddy drying applications at Guwahati weather conditions.